Quality and quantity of leachate in aerobic pilot-scale landfills - Bilgili, MS; Demir, A; Ozkaya, B (SPRINGER, 2006)
In this study, two pilot-scale aerobic landfill reactors with (A1) and without (A2) leachate recirculation are used to obtain detailed information on the quantity and quality of leachate in aerobic landfills. The observed parameters of leachate quality are pH, chloride (Cl-), chemical oxygen demand (COD), biological oxygen demand (BOD), total Kjeldahl nitrogen (TKN), ammonia nitrogen (NH3-N), and nitrate (NO3--N). pH values of the leachate increased to 7 after 50 days in reactor A1 and after 70 days in reactor A2. Cl- concentrations increased rapidly to 6100 (A1) and 6900 (A2) mg/L after 80 days, from initial values of 3000 and 2800 mg/L, respectively. COD and BOD values decreased rapidly in the A1 landfill reactor, indicating the rapid oxidation of organic matter. The BOD/COD ratio indicates that leachate recirculation slightly increases the degradation of solid waste in aerobic landfills. NH3-N concentrations decreased as a result of the nitrification process. Denitrification occurred in parts of the reactors as a result of intermittent aeration; this process causes a decrease in NO3- concentrations. There is a marked difference between the A1 and A2 reactors in terms of leachate quantity. Recirculated leachate made up 53.3% of the leachate generated from the A1 reactor during the experiment, while leachate quantity decreased by 47.3% with recirculation when compared with the aerobic dry landfill reactor.
Keywords: solid waste; landfilling; aerobic landfill; leachate; degradation; MUNICIPAL SOLID-WASTE; ANAEROBICALLY DECOMPOSED REFUSE; METHANE PRODUCTION; BIOGAS PRODUCTION; RECIRCULATION; STABILIZATION; RECYCLE; DESIGN; Environmental Sciences & Ecology